Generic bifurcation of Hamiltonian vector fields with symmetry - Dellnitz, M; Melbourne, I; Marsden, J E (Nonlinearity)

High performance universal hashing, with applications to shared memory simulations - Dietzfelbinger, Martin; Meyer auf der Heide, Friedhelm (Data structures and efficient algorithms)

Hashing strategies for simulating shared memory on distributed memory machines - Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

On the performance of networks with multiple busses - Meyer auf der Heide, Friedhelm; Pham, Hieu Thien (STACS 92)

Efficient PRAM simulation on a distributed memory machine - Karp, Richard M.; Luby, Michael; Meyer auf der Heide, Friedhelm (Proceedings of the twenty-fourth annual ACM symposium on Theory of computing - STOC '92)

Dynamic Hashing in Real Time - Dietzfelbinger, Martin; Meyer auf der Heide, Friedhelm (TEUBNER-TEXTE zur Informatik)

Computational bifurcation of periodic solutions in systems with symmetry - Dellnitz, Michael (IMA Journal of Numerical Analysis)

Die Auswirkungen des Betriebsüberganges nach § 613 a BGB auf die Rechte der Arbeitnehmer - Krimphove, Dieter (Die Verschmelzung von Genossenschaften - insbesondere von Kreditgenossenschaften)

Förderung von Studentinnen im Grundstudium - Oevel, Gudrun; Wagner, M. (Frauen in natur- und ingenieurwissenschaftlichen Berufen)

The Philips Research System for Continuous-Speech Recognition: Overview and Evaluation on the DRAPA RM Task - Aubert, Xavier L.; Ney, Hermann; Haeb-Umbach, Reinhold (DRAPA Speech Workshop)

Improvements in Speech Recognition for Voice Dialling in the Car Environment - Geller, Dieter; Haeb-Umbach, Reinhold; Ney, Hermann (ESCA Workshop on Speech Recognition in Adverse Conditions, Cannes-Mandelieu)

A modified trellis coding technique for partial response channels - Haeb-Umbach, Reinhold (IEEE Transactions on Communications)
The problem of trellis coding for multilevel baseband transmission over partial response channels with transfer polynomials of the form (1+or-D/sup N/) is addressed. The novel method presented here accounts for the channel memory by using multidimensional signal sets and partitioning the signal set present at the noiseless channel output. It is shown that this coding technique can be viewed as a generalization of a well-known procedure for binary signaling: the concatenation of convolutional codes and inner block codes that are tuned to the channel polynomial. It results in high coding gains with moderate complexity if some bandwidth expansion is accepted.

Trellis codes for partial-response magnetooptical direct overwrite recording - Haeb-Umbach, Reinhold; Lynch, Robert (IEEE Journal on Selected Areas in Communications)
The authors present conditions on the error sequences between channel input sequences which guarantee certain lower bounds on the free Euclidian distance at the output of a partial-response (PR) class I or II channel. From these expressions, trellis codes are derived which improve performance of binary signaling over noisy PR channels with reduced complexity maximum-likelihood sequence detection. They are shown to be compatible with the input restriction caused by the magnetooptical resonant coil direct overwrite recording scheme. The codes achieve high signal-to-noise ratio coding gains of 3 dB (on PR class I) and 2.2 dB (on PR class II) with rates as close to, but strictly less than, the capacity of the initial input restriction as desired. The performance of these codes is analyzed with an optical channel simulation system which shows that one code has the rare but highly desirable property that its maximum-likelihood sequence detector (MLSD) is less complex than the MLSD of the reference system and still achieves an error rate performance gain of 1.8 dB

Linear Discriminant Analysis for Improved Large Vocabulary Continuous Speech Recognition - Haeb-Umbach, Reinhold; Ney, Hermann (ICASSP, San Francisco)
The interaction of linear discriminant analysis (LDA) and a modeling approach using continuous Laplacian mixture density HMM is studied experimentally. The largest improvements in speech recognition could be obtained when the classes for the LDA transform were defined to be sub-phone units. On a 12000 word German recognition task with small overlap between training and test vocabulary a reduction in error rate by one-fifth was achieved compared to the case without LDA. On the development set of the DARPA RM1 task the error rate was reduced by one-third. For the DARPA speaker-dependent no-grammar case, the error rate averaged over 12 speakers was 9.9%. This was achieved with a recognizer using LDA and a set of only 47 Viterbi-trained context-independent phonemes.

Improvements in Beam Search for 10,000-Word-Continuous Speech Recognition - Ney, Hermann; Haeb-Umbach, Reinhold; Tran, B. H.; Oerder, Martin (ICASSP, San Francisco)
This paper describes the improvements in a time synchronous beam search strategy for a 10000-word continuous speech recognition task. The improvements are based on two measures: a tree-organization of the pronunciation lexicon and a novel look-ahead technique at the phoneme level, both of which interact directly with the detailed search at the state levels of the phoneme models. Experimental tests were performed for four speakers on a 12306-word task. As a result of the above measures, the overall search effort was reduced by a factor of 17 without a loss in recognition accuracy.

Generation of Vector Patterns through Reseeding of Multiple-Polynomial LFSRs - Hellebrand, Sybille; Tarnick, Steffen; Rajski, Janusz; Courtois, Bernard

Software design and development in a scientific environment: lessons learned during the development of STAR, an astrophysical analysis and visualization package - Domik, Gitta O; Mickus-Miceli, Kristina D (Astronomical Data Analysis Software and Systems I)

Visualization of Multi-dimensional Arrays in Astronomy - Domik, Gitta (European Southern Observatory Conference and Workshop Proceedings)

An Enriched Framework for Multidisciplinary Data Analysis - Mickus-Miceli, KD; Domik, G (Symposium on Intelligent Scientific Computation, American Association for Artificial Intelligence (AAAI), Fall 1992 Symposium Series, Cambridge MA, October)

Europäische Fusionskontrolle - Krimphove, Dieter

Anlageberatung Das System der zivilrechtlichen Haftung von Kreditinstituten - Krimphove, Dieter

Generation of Vector Patterns through Reseeding of Multiple-Polynomial LFSRs - Hellebrand, Sybille; Tarnick, Steffen; Rajski, Janusz; Courtois, Bernard
Keywords: WORKSHOP

Generation of Vector Patterns through Reseeding of Multiple-Polynomial LFSRs - Hellebrand, Sybille; Tarnick, Steffen; Rajski, Janusz; Courtois, Bernard
Keywords: WORKSHOP

Complexity results for the default- and autoepistemic logic - Steffen, Eckhard (Computer Science Logic)

Experimental Results to Interprocessor Communication in Distributed Transputer-Systems - Ginthör, Robert; Platzner, Marco; Weiss, Reinhold (Proceedings of the 1st Austrian-Hungarian Workshop on Transputer Applications)

Contribution to the AC-analysis of resonant converters; analysis of the series-parallel resonant converter including effects of parasitics and lossless snubbers for optimized design - Fröhleke, Norbert; Kunze, Jürgen; Fiedler, A.; Grotstollen, Horst (APEC '92 Seventh Annual Applied Power Electronics Conference and Exposition)

Resonant power supply for barrier discharge UV-excimer sources - Kunze, Jürgen; Fröhleke, Norbert; Grotstollen, Horst; Margaritis, Basile; Locken, F. (Conference Record of the 1992 IEEE Industry Applications Society Annual Meeting)

Hilbert, Zermelo und die Institutionalisierung der mathematischen Logik in Deutschland - Peckhaus, Volker (Berichte zur Wissenschaftsgeschichte)
Rezensionen: MR 93d:01046 (Charles F. Kielkopf); Zbl. Math. 756.01034 (I. Grattan-Guinness).

Wozu Algebra der Logik? Zum Lebenswerk von Ernst Schröder [Abstract] - Peckhaus, Volker (III. Österreichisches Symposion zur Geschichte der Mathematik. Neuhofen an der Ybbs, 8. bis 14. November 1992. Umwege, Abschneider und Sackgassen ... über Abweichungen vom „normalen“ Gang der Entwicklung. Kurzfassungen der Vorträge)

Arithmetik — Logik — absolute Algebra. E. Schröders Suche nach einer universalen Theorie der Verknüpfungen [Abstract] - Peckhaus, Volker (Deutsche Mathematiker-Vereinigung. Jahrestagung 13.–18.9.1992 in Berlin. Vortragsauszüge)

Topologien und Schalterkonzepte für Schaltnetzteile hoher Leistung bei geringer Ausgangsspannung - Fröhleke, Norbert

Pulswechselrichtergespeiste Drehstromantriebe unter Berücksichtigung des Stromlückens - Wang, Yongfan

The Pseudoexhaustive Test of Sequential Circuits - Wunderlich, Hans-Joachim; Hellebrand, Sybille (IEEE Transactions on Computer-Aided Design of Integrated Circuits and Systems (TCAD))

Generation of Vector Patterns through Reseeding of Multiple-Polynomial Linear Feedback Shift Registers - Hellebrand, Sybille; Tarnick, Steffen; Rajski, Janusz; Courtois, Bernard (IEEE International Test Conference (ITC'92))

Die Aktualgenese von Raummodellen und ihr Einfluß auf die Linearisierung - Buhl, Engelbert; Buhl, Heike M.

Forschungsergebnisse zur Geschlechterfrage - Konsequenzen für die Gestaltung von Unterricht sowie für die Aus- und Weiterbildung von Lehrkräften - Bigga, Regine (Lehrplanrevision in Schleswig-Holstein)

The EXPRESS Information Modeling Workbench - A New Approach to Graphical Design Environments - Müller, Wolfgang; Kleinjohann, Bernd (Proceedings of the 2nd EXPRESS User's Group Conference)

DIRECT MODULATION 565 MBIT/S OPTICAL PSK HETERODYNE SYSTEM WITH SOLITARY SL-QW-DFB LASERS USING NOVEL SUPPRESSION OF PHASE-TRANSITION PERIODS IN CARRIER RECOVERY - MEISSNER, E; Noé, Reinhold; BORCHERT, B; RODLER, H (ELECTRONICS LETTERS)

FULLY ENGINEERED COHERENT MULTICHANNEL TRANSMITTERS AND RECEIVERS WITH LOW-COST POTENTIAL - Noé, Reinhold; RODLER, H; EBBERG, A; MEISSNER, E; BODLAJ, V; DROGEMULLER, K; WITTMANN, J (ELECTRONICS LETTERS)

ACCURATE AND SIMPLE OPTICAL FREQUENCY STABILIZATION FOR A COHERENT MULTICHANNEL SYSTEM - Noé, Reinhold; DROGEMULLER, K (IEEE PHOTONICS TECHNOLOGY LETTERS)

Chromaticity of polymer-dispersed cholesteric liquid crystals - Kitzerow, Heinz-Siegfried; Crooker, P. P.; Heppke, G. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Behaviour of polymer dispersed cholesteric droplets with negative dielectric anisotropy in electric fields - Kitzerow, Heinz-Siegfried; Crooker, P. P. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Microscopic observations of axial and radial nematic droplets for a dual-frequency addressable liquid crystal - Kitzerow, Heinz-Siegfried; Xu, F.; Crooker, P. P. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

DIRECT MODULATION 565 MB/S DPSK EXPERIMENT WITH 62.3 DB LOSS SPAN AND ENDLESS POLARIZATION CONTROL - Noé, Reinhold; MEISSNER, E; BORCHERT, B; RODLER, H (IEEE PHOTONICS TECHNOLOGY LETTERS)

Electrostriction dynamics of blue phase II crystallites - Kitzerow, Heinz-Siegfried; Crooker, P. P.; Rand, J.; Xu, J.; Heppke, G. (Journal de Physique II)
Keywords: Physics and Astronomy (miscellaneous); General Engineering; Atomic and Molecular Physics; and Optics

Dynamic response of a blue phase to an applied field - Dolganov, V. K.; Heppke, G.; Kitzerow, Heinz-Siegfried (Journal de Physique II)
Keywords: Physics and Astronomy (miscellaneous); General Engineering; Atomic and Molecular Physics; and Optics

Dynamics of polymer-dispersed cholesteric liquid crystals - Kitzerow, Heinz-Siegfried; Rand, J.; Crooker, P. P. (Journal de Physique II)
Keywords: Physics and Astronomy (miscellaneous); General Engineering; Atomic and Molecular Physics; and Optics

Electric-field effects on nematic droplets with negative dielectric anisotropy - Xu, F.; Kitzerow, Heinz-Siegfried; Crooker, P. P. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Linear electro‐optic effects in polymer‐dispersed ferroelectric liquid crystals - Kitzerow, Heinz-Siegfried; Molsen, Henning; Heppke, Gerd (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Helical unwinding in polymer-dispersed ferroelectric liquid crystals - Kitzerow, Heinz-Siegfried; Molsen, Henning; Heppke, Gerd (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics